2021
DOI: 10.31234/osf.io/pqct5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Psychological Impact of COVID-19 Pandemic Lockdowns: A Review and Meta-Analysis of Longitudinal Studies and Natural Experiments

Abstract: Lockdowns to control the spread of the coronavirus disease 2019 (COVID-19) have had profound effects on everyday life worldwide, but their effect on mental health remains unclear because available meta-analyses and reviews rely mostly on cross-sectional studies. We conducted a rapid review and meta-analysis of longitudinal studies and natural experiments investigating the relationship between COVID-19 lockdowns and mental health. A total of 25 studies involving 72,004 participants and 58 effect sizes were anal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
124
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(143 citation statements)
references
References 50 publications
12
124
0
5
Order By: Relevance
“…Loneliness exerted more impact on depressive and post-traumatic stress symptoms, which can be explained by the deprivation of relationships, while to be accompanied was more relevant than to be alone regarding stress. Prati and Mancini (2021), meta-analyzed 25 recent studies on the impact of the COVID-19 pandemic on population mental health, and concluded that the psychological impact of social restrictions is small in magnitude and highly heterogeneous (Prati and Mancini, 2021). In our study, in fact social distancing played a secondary role to the explanation of the symptoms comparing the effect sizes with the main predictors, but the containment measures applied may had indirect effects, which were measured by other variables, i.e., economic problems and emotional abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness exerted more impact on depressive and post-traumatic stress symptoms, which can be explained by the deprivation of relationships, while to be accompanied was more relevant than to be alone regarding stress. Prati and Mancini (2021), meta-analyzed 25 recent studies on the impact of the COVID-19 pandemic on population mental health, and concluded that the psychological impact of social restrictions is small in magnitude and highly heterogeneous (Prati and Mancini, 2021). In our study, in fact social distancing played a secondary role to the explanation of the symptoms comparing the effect sizes with the main predictors, but the containment measures applied may had indirect effects, which were measured by other variables, i.e., economic problems and emotional abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies have reported that rates of psychological distress increased during the early stages of the COVID-19 pandemic [5][6][7][8] . A rapid review and meta-analysis of 12 longitudinal studies with pre-pandemic data found small but significant increases in the rates of depressive symptoms (Hedge's g = 0.15, SE = 0.07, 95% CI 0.01 to 0.30, p = .037) and anxiety (g = 0.17, SE = 0.05, 95% CI 0.07 to 0.27, p < .001) during lockdown (January to June 2020), when compared to before the pandemic 9 .…”
Section: Introductionmentioning
confidence: 91%
“…Staying home and working from home during the pandemic have implications for daily life ranging from dealing with economic impairment (i.e., job/income loss) [ 12 ] and work-overload [ 13 ] to increased parenting demands (i.e., child care and homeschooling). In addition to all these abrupt changes in daily life, the pandemic has left many people without access to adaptive coping resources, such as social support from family and friends and access to recreational facilities, health and counseling services and places of worship [ 12 , 14 ]. Previous research has shown that changes in these lifestyle-behaviors during lockdowns, or when more severe social distancing restrictions are in place, are associated with adverse psychological effects [ 10 , 15 ] impacting mental health and wellbeing [ 16 , 17 , 18 ], alongside more stress [ 19 ] and anxiety [ 20 ].…”
Section: Introductionmentioning
confidence: 99%